Predictors of Reading Comprehension in Children With Cochlear Implants - Wass, Malin; Anmyr, Lena; Lyxell, Björn; Östlund, Elisabet; Karltorp, Eva; Löfkvist, Ulrika (Frontiers in Psychology, 2019)
Children with a profound hearing loss who have been implanted with cochlear implants, vary in terms of their language and reading skills. Some of these children have strong language skills and are proficient readers whereas others struggle with language and both the decoding and comprehension aspects of reading. Reading comprehension is dependent on a number of skills where decoding, spoken language comprehension and receptive vocabulary have been found to be the strongest predictors of performance. Children with CI have generally been found to perform more poorly than typically hearing peers on most predictors of reading comprehension including word decoding, vocabulary and spoken language comprehension, as well as working memory. The purpose of the current study was to investigate the relationships between reading comprehension and a number of predictor variables in a sample of twenty-nine 11-12-year-old children with profound hearing loss, fitted with CI. We were particularly interested in the extent to which reading comprehension in children with CI at this age is dependent on decoding and receptive vocabulary. The predictor variables that we set out to study were word decoding, receptive vocabulary, phonological skills, and working memory. A second purpose was to explore the relationships between reading comprehension and demographic factors, i.e. parental education, speech perception and age of implantation. The results from these 29 children indicate that receptive vocabulary is the most influential predictor of reading comprehension in this group of children although phonological decoding is, of course, fundamental.